2020
DOI: 10.24331/ijere.672425
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Interactions of Mothers and Their 30-42 Months Old Children who are Living in Different Family Types in the Context of Mother Sensitivity

Abstract: This study was conducted to investigate the interactions of mothers and 30-42 months old children living in large and nuclear family types in the context of maternal sensitivity. In this study, one of the qualitative research methods, embedded multi-case research was used. The participants of the study consisted of 8 mothers living in 4 large-4 nuclear family types and their children aged 30-42 months in the town of Muş. Descriptive-interpretive data analysis was used to describe the interactions of the studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This study overlaps with finding of Seven (2017) that mothers' eye contact attempts in mother-child interaction often end in failure. The fact that majority of children's messages are not noticed by mothers was reported in another study dealing with sensitivity of mothers (Seven & Alabay, 2020). It is also considered that frequent eye contact attempts of mothers were found preventive of the game by children.…”
Section: Discussion and Suggestionsmentioning
confidence: 91%
“…This study overlaps with finding of Seven (2017) that mothers' eye contact attempts in mother-child interaction often end in failure. The fact that majority of children's messages are not noticed by mothers was reported in another study dealing with sensitivity of mothers (Seven & Alabay, 2020). It is also considered that frequent eye contact attempts of mothers were found preventive of the game by children.…”
Section: Discussion and Suggestionsmentioning
confidence: 91%
“…The nuclear family has emerged as the dominant family type in Turkish society in the last 50 years. However, studies in recent years have found that parents in nuclear families continue to display many behaviours related to the roles in the extended family (Seven & Alabay, 2020). Ilhan-Ildız and Seven (2018) revealed in their study that parents continued extended family attitudes and behaviour patterns towards their children regardless of the dominance of the nuclear family type in Turkish culture.…”
Section: Introductionmentioning
confidence: 95%
“…The predictability of mothers is an important quality for secure attachment. As the infants grow, positive synchrony is supported by various activities such as eye contact, face-to-face interaction, peek-aboo and other games, playing with toys, tidying the house together and preparing meals together (Cohn & Elmore, 1988;Seven & Alabay, 2020).…”
Section: Introductionmentioning
confidence: 99%